Solar Tracker Enhances Energy Yield by Over 35%: Pelacak Tenaga Surya Meningkatkan Hasil Energi Lebih dari 35% - Azmi , Muhammad Zum’an; Syahrorini, Syamsudduha; Anshory , Izza; Ayuni , Shazana Dhiya (Universitas Muhammadiyah Sidoarjo, 2024)
The escalating demand for electricity, coupled with Indonesia's commitment to expanding renewable energy sources, particularly solar power, underscores the necessity for innovative approaches in optimizing solar energy utilization. This paper addresses the deficiency in traditional fixed-angle solar panels, which fail to harness solar energy efficiently due to their inability to track the sun's movement. Through a comprehensive study utilizing literature review and system design, this research aims to develop an advanced solar tracker system to enhance energy production. The proposed solar tracker employs a scanning method to adjust panel orientation every hour, ensuring optimal sunlight absorption throughout the day. The methodology encompasses literature review, system design, and partial testing to evaluate sensor functionality, battery charging circuit, real-time clock module, and stepper motor driver. Results indicate that the solar tracker system increases electricity generation by 35.53% compared to fixed-angle panels, demonstrating its efficacy in maximizing solar energy utilization. Furthermore, the system's ability to adapt to changing weather conditions underscores its potential for practical implementation in renewable energy initiatives, thereby contributing to sustainable energy development. Highlight: Energy boost: Solar tracker increases electricity generation by 35.53%. Adaptive design: Scans hourly for optimal sunlight absorption. Practicality: Suitable for real-world renewable energy applications. Keywoard: Solar tracker, Renewable energy, Energy optimization, System design, Electrical efficiency